Revision rhinoplasty with free diced cartilage grafts: Outcome evaluations with the Nasal Obstruction Symptom Evaluation (NOSE) scale: Outcome of revision rhinoplasty - Kandulu, Hüseyin (Journal of Surgery and Medicine, 2023)
Background/Aim: The Nasal Obstruction Symptom Evaluation (NOSE) scale is a validated, reliable, and feasible instrument used to evaluate nasal obstruction severity. We aimed to assess patient satisfaction using the NOSE score after revision rhinoplasty with free diced cartilage (fDC) grafts. Methods: In this cross-sectional study, 36 patients who underwent a revision rhinoplasty procedure completed the Turkish version of the NOSE questionnaire before and six months after rhinoplasty. Pre- and postoperative NOSE scores were compared using the Mann Whitney U test. Results: The pre- and postoperative total mean NOSE scores were 68.06 and 8.47, respectively. The NOSE score significantly decreased six months after rhinoplasty surgery (P<0.001). Adapting to exercise was the parameter with the highest improvement rate. Conclusion: The outcome of the NOSE questionnaires in patients with nasal deformities shows that a revision rhinoplasty surgery with the placement of fDC grafts contributes to the improvement of nasal functions. The Turkish version of the NOSE scale is a useful tool to assess patient satisfaction among the Turkish population.